Combining BRITE and ground-based photometry for the β Cephei star ν Eridani: impact on photometric pulsation mode identification and detection of several g modes. Issue 2 (4th October 2016) - Handler, G.; Rybicka, M.; Popowicz, A.; Pigulski, A.; Kuschnig, R.; Zocłońska, E.; Moffat, A. F. J.; Weiss, W. W.; Grant, C. C.; Pablo, H.; Whittaker, G. N.; Ruciński, S. M.; et al.
Abstract: We report a simultaneous ground- and space-based photometric study of the β Cephei star ν Eridani. Half a year of observations have been obtained by four of the five satellites constituting BRITE-Constellation, supplemented with ground-based photoelectric photometry. We show that carefully combining the two data sets virtually eliminates the aliasing problem that often hampers time series analyses. We detect 40 periodic signals intrinsic to the star in the light curves. Despite a lower detection limit, we do not recover all the pressure and mixed modes previously reported in the literature, but we newly detect six additional gravity modes. This behaviour is a consequence of temporal changes in the pulsation amplitudes that we also detected for some of the p modes. We point out that the dependence of theoretically predicted pulsation amplitude on wavelength is steeper in visual passbands than those observationally measured, to the extent that three dominant pulsation modes of ν Eridani would be incorrectly identified using data in optical filters only. We discuss possible reasons for this discrepancy.